Kuwait : Fostering Sustainable Investment through Modern Commercial Law Systems - Mako, William; Mokal, Riz; Cojocaru, Iulia; Johnson, Gordon W. (World Bank, Washington, DC, 2013)
The Government of Kuwait (GOK) is now moving decisively to reform its insolvency and creditor/debtor regime (ICR). Stakeholders recognize that Kuwait's ICR system had fallen behind that required for a modern economy. The GOK's effort to establish a modern insolvency and creditor rights system is driven by several considerations: first, consistent with its traditional strengths, Kuwait is seeking to transform itself into a regional financial and trading center, as expressed in the Amiri vision 2030 and the GOK's most-recent five-year development plan. Second, many of the difficulties afflicting the country's investment company sector, which started surfacing in 2008, still await fundamental resolution. Third, development of small and medium enterprises (SMEs) is essential to help the GOK meet its goals of diversifying the sources of income and encouraging young people to work in the private sector, in order to reduce the burden of the public sector. The GOK's reform agenda aspires to world-class standards, balancing international norms with solutions rooted in Kuwait's unique local customs. The consensus among stakeholders is that an effective insolvency regime would benefit the Kuwait economy.